2010
DOI: 10.1007/s11010-010-0568-5
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A1 and A3 receptor agonists reduce hypoxic injury through the involvement of P38 MAPK

Abstract: Activation of either the A(1) adenosine receptor (A(1)R) or the A(3) adenosine receptor (A(3)R), by their specific agonists CCPA and Cl-IB-MECA, respectively, protects cardiac cells in culture against ischemic injury. Yet the full protective mechanism remains unclear. In this study, we therefore examined the involvement of p38 mitogen-activated protein kinase (MAPK) and extracellular signal-regulated kinases (ERK) phosphorylation in this protective intracellular signaling mechanism. Furthermore, we investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…This pathway has also been observed in A 3 AR-stimulated activity of antidepressant-sensitive serotonin transporters (Zhu et al, 2011). A 3 AR activation protects cardiomyocytes from hypoxia via phosphorylation of p38 MAPK, located downstream of the mitochondrial K ATP channel opening (Leshem-Lev et al, 2010). Accordingly, increased phosphorylation of p38 has been found after Cl-IB-MECA treatment, which proves beneficial, protecting the rat heart subjected to ischemia (Hochhauser et al, 2007).…”
Section: Intracellular Pathways Regulated By the Amentioning
confidence: 71%
“…This pathway has also been observed in A 3 AR-stimulated activity of antidepressant-sensitive serotonin transporters (Zhu et al, 2011). A 3 AR activation protects cardiomyocytes from hypoxia via phosphorylation of p38 MAPK, located downstream of the mitochondrial K ATP channel opening (Leshem-Lev et al, 2010). Accordingly, increased phosphorylation of p38 has been found after Cl-IB-MECA treatment, which proves beneficial, protecting the rat heart subjected to ischemia (Hochhauser et al, 2007).…”
Section: Intracellular Pathways Regulated By the Amentioning
confidence: 71%
“…Endogenous adenosine makes a significant contribution to A 1 agonistmediated prevention of necrosis in a cardiac cell model of ischemia by cooperative interactions with both A 2A and A 2B receptors, but does not play a role in A 3 agonistmediated protection (Urmaliya et al, 2009;Methner et al, 2010). It was reported that A 1 and A 3 receptor agonists reduce hypoxic injury through the involvement of p38 MAPK (Leshem-Lev et al, 2010). Adenosine stimulates the recruitment of endothelial progenitor cells to the ischemic heart to enhance revascularization (Goretti et al, 2012).…”
Section: Ischemiamentioning
confidence: 99%
“…It has been reported that A1R and A3R agonists reduce hypoxic injury through the involvement of p38 MAPK [553]. In situ ischaemic pre-conditioning conferred cardioprotection in A1R, A2AR and A3R, but not A2BR knockout mice, or in wild-type mice after inhibition of A2BR, and thus, it was suggested that 5′-nucleotidase and A2BR agonists might be considered as therapeutic agents for myocardial ischaemia [554,555].…”
Section: Ischaemiamentioning
confidence: 99%